2005
DOI: 10.1128/jvi.79.24.15578-15581.2005
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus (HCV) and Hepatitis B Virus (HBV) Can Coinfect the Same Hepatocyte in the Liver of Patients with Chronic HCV and Occult HBV Infection

Abstract: In this work, we have shown that hepatitis C virus (HCV) and hepatitis B virus (HBV) can coexist in the same hepatocyte using double fluorescent in situ hybridization in liver biopsy samples from patients with chronic HCV infection with occult HBV infection. Digital image analysis of hybridization signals showed that the HBV DNA levels in coinfected hepatocytes were lower than those in cells infected only with HBV. This finding supports the hypothesis of inhibition of HBV replication by HCV. Furthermore, HCV R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 22 publications
3
36
0
5
Order By: Relevance
“…mentioned, HBV and HCV can coexist in the same hepatocyte in the liver of chronic hepatitis C patients with occult HBV infection [72]. The immunobiology of this clinical situation [23,35] and that of occult HBV plus occult HCV dual infection have not been studied in detail.…”
Section: Occult Hbv and Hcv Co-infectionmentioning
confidence: 98%
See 1 more Smart Citation
“…mentioned, HBV and HCV can coexist in the same hepatocyte in the liver of chronic hepatitis C patients with occult HBV infection [72]. The immunobiology of this clinical situation [23,35] and that of occult HBV plus occult HCV dual infection have not been studied in detail.…”
Section: Occult Hbv and Hcv Co-infectionmentioning
confidence: 98%
“…In this regard, transfection studies have shown that core and NS2 HCV proteins inhibit HBV replication and gene expression in vitro [68][69][70][71]. As it has been demonstrated that HBV and HCV coexist in the same hepatocyte in the liver of patients with chronic hepatitis C and occult HBV infection [72], it may be speculated that the molecular mechanism by which HCV proteins inhibit HBV replication and gene expression in vitro may also operate in vivo.…”
Section: Molecular Mechanisms Of Occult Hbv Infectionmentioning
confidence: 99%
“…Despite evidence to suggest that both HBV and HCV can replicate in the same hepatocyte in vivo [13], there is little information regarding interaction(s) between the two viruses at the molecular level that may explain observations of viral dominance in the clinic. However in vitro studies have demonstrated that over-expression of HCV core or NS5A proteins suppresses HBV gene expression and replication [14][15][16][17], with the latter inhibiting HBV replication via its ability to activate phosphatidylinositol-3-OH kinase (PI-3K)/Akt signalling.…”
Section: Introductionmentioning
confidence: 95%
“…Interference with HBV replication by HCV can take place if both viruses coexist in the same hepatocyte. Double fluorescent in situ hybridization was used to understand the role of HCV in inhibiting HBV replication in 6 liver biopsy specimens from patients with chronic HCV and occult HBV infection (224). The intensities of fluorescence signals corresponding to HBV DNA and HCV RNA were measured in singly infected and doubly infected hepatocytes using digital image analysis.…”
Section: Coinfection With Other Microbesmentioning
confidence: 99%